The Effect of concern about Reported Income on Discretionary Spending Decisions: The Case of Research and Development - Baber, William R.; Fairfield, Patricia M.; Haggard, James A. (The Accounting Review, 1991)
[This study investigates whether concern about reporting favorable trends in accounting net income influences decisions to invest in research and development (R&D). Using data for 438 U.S. industrial firms during the period 1977-1987, the analysis indicates that relative R&D spending is significantly less when spending jeopardizes the ability to report positive or increasing income in the current period. Unlike related studies that consider choices among alternative accounting practices (DeAngelo 1986; Healy 1985; Liberty and Zimmerman 1986; McNichols and Wilson 1989; Moses 1987), this study focuses on investment decisions as instruments for achieving income objectives. In most instances, choices among accounting practices have no direct cash flow consequences, but changes in R&D spending to satisfy current-period income objectives do alter cash flows. The evidence is consistent with assertions that U.S. manufacturing firms are not competitive internationally in part because U.S. managers are overly concerned about how their R&D investment decisions affect current-period earnings (see, e.g., Markoff 1990). We analyze capital spending to determine whether these R&D reductions reflect differences in investment opportunities or incentives rather than differences in accounting treatment. Unlike the results for R&D, differences in capitalized costs among firms in the sample are not statistically significant. We also consider whether the results can be attributed to accounting-based compensation arrangements. For this purpose, we examine a sample of firms with no accounting-based management compensation contracts in effect during the test period. Results are comparable to those obtained for the entire sample, which is inconsistent with an explanation that the observed differences in R&D spending are attributable only to explicit compensation arrangements. Our results are consistent with conclusions that compliance with SFAS No. 2 (FASB 1974) discouraged investment in R&D (Elliott et. al. 1984; Horwitz and Kolodny 1980). That is, the evidence suggests that managers are more likely to consider current-period income effects when making R&D decisions than when making capital-spending decisions, whose costs are amortized over a number of accounting periods.]